Dissonant Heritages and Memories in Contemporary Europe - Lähdesmäki, Tuuli; Passerini, Luisa; Kaasik-Krogerus, Sigrid; van Huis, Iris (Palgrave Studies in Cultural Heritage and Conflict, 2019)
This open access book discusses political, economic, social, and humanitarian challenges that influence both how people deal with their past and how they build their identities in contemporary Europe. Ongoing debates on migration, on local, national, inter- and transnational levels, prove that it is a divisive issue with regards to understanding European integration and identity. At the same time, the European Union increasingly invests in projects related to European heritage, museums, and cultural memory networks, while having to take dissonant heritages into account. These processes in their combination offer an interesting dynamic and form the complex puzzle that poses challenging questions for anyone involved in academic research, heritage practices, and policy debates. With this puzzle at its core, this book explicitly focuses on slippery and transforming notions of Europe and critically discusses ongoing and transforming power structures of heritage and memory in today's Europe. The book combines theoretical and methodological contributions to the debates on European heritage and memory studies and in-depth analyses of empirical case studies. Its main aim is to bring research fields concerning memory and heritage into a closer dialogue and thus explore the cultural and political dynamics of contemporary Europe.